THE INFLUENCE OF WORK ENVIRONMENT AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE KARAWANG REGENCY HEALTH SERVICE - Dhiya Aulia Azzahra; Asep Jamaludin; Nandang (PT. Berkah Digital Teknologi, 2025)
Purpose: The purpose of this study is to determine the effect of work environment and work discipline on employee performance at the Karawang Regency Health Office Research Methodology: The research method used is a quantitative approach. The sampling method used is random sampling by distributing questionnaires to a population of 102 respondents and taking a sample of 81 respondents using the Slovin formula. The study used multiple regression analysis techniques using SPSS version 27 software. The data analysis used includes validity, reliability, normality, multicollinearity, heteroscedasticity, autocorrelation, partial t-test, and simultaneous f-test. Results: The results of this study prove that there is a partial influence of the Work Environment (X1) on Employee Performance (Y) with a sig value of 0.000 < 0.05, and there is no partial influence of Work Discipline (X2) on Employee Performance (Y) with a sig value of 0.395 > 0.05. Additionally, there is a simultaneous influence of the Work Environment (X1) and Work Discipline (X2) on Employee Performance with a sig value of 0.000 < 0.05. Limitations: The study was limited to the Karawang Regency Health Office, and the data collection was done through a questionnaire, which may have limitations in capturing the full context of the respondents' perspectives. Contribution: The findings of this study provide insights into the importance of the work environment and work discipline in improving employee performance, which can be useful for management in developing strategies to enhance organizational effectiveness.